"In the street they're real, in a picture they're not": Constructions of children and childhood among users of online child sexual exploitation material. (April 2019) - Rimer, Jonah R.
Abstract: Background: Research about online child sexual exploitation material (CSEM) users focuses on psychological assessments, demographics, motivations, and offending rates. Little is known about their understandings of children in CSEM. Objective: From an anthropological perspective, examine CSEM users' constructions of children and childhood online and offline, and explore how these factor into their crimes. Participants and setting: CSEM users in UK group programs. Methods: In-depth ethnography, including 17 months of participant observation in group programs with 81 CSEM users, 31 semi-structured interviews with group participants, and inductive analysis of themes illuminated by childhood theory from anthropology. Results: When referring to children offline, many participants claimed to align with Euro-American norms and constructions surrounding children's learning, protection, irrationality, inexperience, asexuality, and innocence. However online, many constructed children differently: as less or not "real, " and as sexualized. This rendered children in CSEM fundamentally different, which facilitated offending, assisted in overcoming barriers, and allowed participants to hold conventional beliefs about children and childhood while engaging in incongruent online activity. Vital in this process was Internet use and associated distancing, detachment, anonymity, and cultural othering. The program used victim empathy to restore dominant norms to online children, for which participants invoked feelings, recognized their role in abuse, extrapolated consequences for victims, and reinforced norms. Conclusions: Constructions of children and childhood were central in offending. The complexities of negotiating "real" versus "not real" in both offending and victim empathy are discussed, as are conceptual distinctions between "constructions" and "cognitive distortions, " and implications for treatment and prevention.